Catalyst-free large-scale synthesis of composite SiC@SiO2/carbon nanofiber mats by blow-spinning. Issue 48 (20th November 2019) - Chen, Yang; Wang, Ning; Jensen, Martin; Han, Shan; Li, Xianfeng; Li, Wei; Zhang, Xingxiang
Abstract : A robust photocatalytic composite SiC/SiO2 nanofiber/carbon nanofiber mat is prepared via blow-spinning followed by calcination in absence of metal catalysts. Abstract : One-dimensional (1D) SiC nanostructures have attracted considerable interest owing to their unique structure and excellent performance, but nanostructure entanglement limits their application. In this work, a robust photocatalytic composite SiC@SiO2 /carbon nanofiber mat (SiC@CNFMs) is prepared via facile and environmentally friendly blow-spinning (BLS) followed by calcination in absence of metal catalysts. The several hundred micron long as-prepared nanocrystal structures consist of a single-crystalline β-SiC core (diameter between 30–150 nm) and an ultra-thin (8 nm) amorphous SiO2 shell layer. The growth process of the SiC/SiO2 nanofiber is in good agreement with the vapor–solid (VS) mechanism. The synthesized SiC@CNFMs exhibit excellent photodegradation of dyes and due to the utilization of PAN-based carbon nanofiber mats, they show good recycling performance with a dye degradation above 88–95% after 5 cycles. Lastly, the synthesized SiC@CNFMs show high chemical stability under both alkaline and acidic conditions. From these properties, the synthesized SiC@CNFMs show promising potential for wastewater cleaning.